Analysis and prospects for the implementation of STEM education in the educational process of a higher school - Zinovieva, Olha; Lubko, Dmytro; Зінов’єва, Ольга Геннадіївна; Лубко, Дмитро Вікторович (Запоріжжя : 2024, 2024)
EN: This article analyses and considers the prospects for introducing STEM education into the educational process for higher education students. Today, special attention is focused on STEM education as a useful and powerful means of acquiring new skills and gaining practical experience. The main advantage of STEM education for students is their preparation for real life. All of this is very important for the development of a young, modern and active person who plans to realize themselves in life and find a high-paying job in the future. UN: У статті проаналізовано та розглянуто перспективи впровадження STEM освіти в навчальний процес студентів вищих навчальних закладів. Сьогодні особлива увага приділяється STEM освіті як корисному та потужному засобу здобуття нових навичок та практичного досвіду. Основна перевага STEM освіти для здобувачів вищої освіти полягає у підготовці до реального життя. Все це дуже важливо для розвитку молодої, сучасної та активної людини, яка планує реалізувати себе в житті та знайти в майбутньому високооплачувану роботу.
Аналіз та перспективи впровадження STEM освіти в освітній процес вищої школи
Keywords: STEM education; students; educational process; benefits; здобувачі вищої освіти; освітній процес; переваги; STEM освіта